The Development and Validation of a Perceived Nursing Support Scale for Mothers of Preterm Infants - Im, Mihae; Oh, Jina (Asian nursing research, 2021)
Many studies have maintained that nursing support is necessary and essential for mothers of preterm infants; however, the perceived nursing support for mothers of preterm infants has not been sufficiently measured. This study aimed to develop a perceived nursing support scale for mothers of preterm infants (PNSS-MP). The preliminary items of the PNSS-MP were developed through a literature review and in-depth interviews with mothers of preterm infants. Content and face validities were assessed by experts and mothers of preterm infants. A pilot study was conducted to confirm the feasibility and comprehension of the scale. To validate the PNSS-MP, 223 mothers of preterm infants were surveyed. Exploratory factor analyses were performed to confirm construct validity. Convergent and discriminant validities were analyzed using a multitrait-multimethod (MTMM) matrix. Reliability was tested by calculating Cronbach’s α and performing split-half testing. The PNSS-MP consisted of 27 items and was categorized into five factors, explaining 65.3% of the total variance. The factors were named: “baby care support” (7 items), “mental care support” (6 items), “maternal role support” (6 items), “introducing resources support” (4 items), and “information delivery support” (4 items). The overall reliability of the scale was .95. The PNSS-MP adequately reflected the neonatal intensive care unit (NICU) in South Korea. Additionally, the PNSS-MP proved relatively valid and reliable; therefore, it can be used to measure nursing support in the NICU.